Infection Prevention and Control in Healthcare Facilities During the Covid-19 Pandemic in Ghana - Ababio Bannor, Philip; Amfo-Otu, Richard; Akyeampong, Enoch; Affordofe, Michael; Alhassan, Yakubu; Tengey, Senam; Danso, Doreen; Quansah, Reginald; Akpabey, Joana; Obeng, Lawrence; Owiredu Ayesu, Franklin; Badu, Agyemang; et al. (International Journal of Infection Prevention, 2021)
Background Infection prevention and control system in healthcare facilities is essential in dealing with the spread of infectious diseases, especially during an outbreak period such as the COVID-19 pandemic. Objectives The study assessed the infection prevention and control (IPC) situation in selected healthcare facilities in the Greater Accra and Ashanti Regions of Ghana during the Covid-19 pandemic. Methods This was a multi-facility based cross-sectional study that used a monitoring tool of the Health Facilities Regulatory Agency (HeFRA) of Ghana to collect information on the IPC practices at the peak of the Covid-19 pandemic. Data was gathered from 501 healthcare facilities in the Greater Accra (335) and Ashanti (151) Regions. Descriptive, Chi-square, and multiple logistic regression were performed. All statistical analyses were considered significant at an alpha level of 0.05. Results 50.6% of health facilities were assessed as having good IPC systems in the overall assessment. The majority of the health facilities were evaluated as good on governance/leadership. Similarly, the majority (54.3 %)of the facilities had effective infectious waste management. The assessment levels of governance/leadership, management, quality assurance system, human resource, IPC equipment, and water management were all significantly associated with the adherence to good IPC systems. Conclusion IPC systems in most facilities were assessed as good, but some areas require critical attention to help prevent the spread of infections in healthcare facilities in Ghana. Support systems such as revised policy on IPC, governance/leadership, and infectious waste management infrastructure are needed to strengthen facilities with weak or poor IPC systems.
Keywords: Infection Prevention and Control; Governance; Healthcare Waste Management; Infectious Waste; COVID-19